Comparison of Structural Analysis of Multi-Story Buildings Using the Manual Moment Distribution Method and SAP2000 Application - Rian Permana Putra; Sapna Yusmania; Gilang Novando; Risky Wahyu Pratama (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
Structural analysis of multi-story buildings is essential for ensuring safety, serviceability, and material efficiency. While software-based analysis is widely used, there is limited quantitative comparison between classical manual methods and modern FEM software for low-rise structures relevant to educational and preliminary design purposes. This study evaluates a three-story reinforced concrete frame using the manual Moment Distribution Method and SAP2000 software. Key structural responses, including bending moments, shear forces, axial forces, and top-floor deflections, were compared, and calculation efficiency was assessed. Results show that the manual method produces bending moments, shear forces, and axial forces within 1–4% of SAP2000 values, and top-floor deflection differs by 4%, confirming its reliability for simple frames. SAP2000, however, reduces analysis time from 4–6 hours to 15–30 minutes and enables modeling of complex load combinations and 3D effects. Based on these findings, a hybrid approach using manual verification alongside software analysis is recommended, offering both conceptual understanding for engineers and efficient, accurate design for practical applications.